Designing Organizational Change in Solving Employee Resign Problem in the Middle of Project At ZYX Company in Jakarta - Pratiwi, Widdya; Hendarman, Achmad Fajar (Journal of Business and Management, 2019)
Abstract. The competition among the construction companies will have intense competition. The company should develop its own competitive advantages so the client will be satisfied with the work of the company. Human resources are quite important in construction companies. In this case, a family construction named PT. ZYX has only realized how important it is to manage human resources properly so that their business can continue to run as it should. The company knows that they have shortcomings in managing their human resources. The problem that PT. ZYXÃ‚Â face the situation of their employees in the field who resign in the middle of the project. It will affect the project as a whole. If it continues, then it will damage the image of the company. This research conducted to address the existing problems by implementing organizational change within the company. This research uses semi-structured interviews and non-participant observation. this research produced several issues, there are employee resign, an organizational structure that is not implemented and company changes. In addition, there are other findings from the results of interviews, there is the nepotism that happens in the company, employee loyalty to the company and the problem of official contracts between the company and employees. From the result of the issues, it can be concluded that the main source of the issue is the organizational structure. The company does not implement the organizational structure and the company does not have any specific division to take care of their human resource. The company only has a Personnel Division to take care of the employees' administration. The company needs a Human Resource Division to take care of all the human resource of the company. This Human Resource Division will manage human resource well and solve the existing problem that relates to the employees. In this research, the researcher uses Lewin's Change Model to change the organization and make a new division to the HR Division. So the company needs to change its organizational structure and design new division which is the Human Resource Division.Ã‚Â Keywords: EmployeeResignation, Human Resource, LewinÃ¢â‚¬â„¢s Change Model, Organizational Change, Organizational Structure